2020
DOI: 10.1111/1541-4337.12580
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in processing food powders by using superfine grinding techniques: A review

Abstract: Food powders are ubiquitous in people's daily life and food industry production with numerous advantages. With the increasing use of food powder in the world, it is increasingly important to understand the processing methods of food powder and the changes in physicochemical properties after processing in order to control the processing conditions and the quality of final products. Among the many processing methods for food powders, superfine grinding technique is an emerging and useful tool for superfine powde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 115 publications
(65 citation statements)
references
References 260 publications
2
48
0
1
Order By: Relevance
“…Since chemical fungicides have significant environmental impacts and, moreover, are becoming less effective, the use of wheat straw vinegar seems to be a more effective, low-cost, and natural solution [21]. The results of Gao et al (2020) [21] showed that the application of wheat straw vinegar, diluted 200-fold, significantly decreased the wheat infection rate and deoxynivalenol content by 66% and 69%, respectively. This natural fungicide, given its effectiveness, seems to be very interesting since it is an eco-friendly product that may additionally increase farmers' income by reducing the fungicide costs [21].…”
Section: Wheat Cultivation and Sustainable Agriculture Innovations And Improvements In Wheat Cultivationmentioning
confidence: 99%
See 2 more Smart Citations
“…Since chemical fungicides have significant environmental impacts and, moreover, are becoming less effective, the use of wheat straw vinegar seems to be a more effective, low-cost, and natural solution [21]. The results of Gao et al (2020) [21] showed that the application of wheat straw vinegar, diluted 200-fold, significantly decreased the wheat infection rate and deoxynivalenol content by 66% and 69%, respectively. This natural fungicide, given its effectiveness, seems to be very interesting since it is an eco-friendly product that may additionally increase farmers' income by reducing the fungicide costs [21].…”
Section: Wheat Cultivation and Sustainable Agriculture Innovations And Improvements In Wheat Cultivationmentioning
confidence: 99%
“…The wheat milling process significantly affects flour quality and bread characteristics [25][26][27]. For this reason, the correct management of this unit operation is essential to obtain final products with suitable characteristics [25][26][27].…”
Section: The Importance Of Wheat Conditioning Before Millingmentioning
confidence: 99%
See 1 more Smart Citation
“…P n =P i -P finos (6) %R=P f / P n (7) Donde: P i es el peso inicial de la zanahoria con un diámetro de 5 cm, P finos es el peso de la zanahoria molida con un tamaño menor a 0,5 cm, y P f es el peso final de la zanahoria molida con un tamaño igual a 0,5 cm. Finalmente, el rendimiento y el coeficiente de molienda (∑) del molino de martillos se determinaron mediante las ecuaciones 8 y 9, respectivamente.…”
Section: ) Parámetros Operacionalesunclassified
“…The effectiveness of a mill is determined by its ability to apply sufficient force to fracture or cut the seed into small particles. Within each mill type, there are variations in how forces are applied to the grain (Gao et al., 2020).…”
Section: Introductionmentioning
confidence: 99%